It's Never Too Late or Too Early to Do Science! Programs That Promote Adult–Child Co-Learning in Museums. - Ingber, Jenny; Olson, K.; April, I.; Casado, B. (Journal of Museum Education)
Intergenerational science education programs provide many opportunities to enhance content connection-making, foster classroom community, and cultivate science identity for participants. The Early Adventures Program (EAP) at the American Museum of Natural History (AMNH) serves as a model for adult–child co-learning programs for children (ages 2–5). In this article, we share EAP's program goals and the design principles that work to support those goals. Central to the design of EAP is the emphasis on community and how building a "community of practice" enhances participants' learning experiences. A vignette of an EAP class is included, illustrating the program's design principles in practice. Lastly, we share insights from parents about their own and their children's experiences as participants in the program.